Experience and local memory of older people in the face of disasters: a systematic review - Navarrete-Valladares, Camila; Sandoval-Díaz, José; Sandoval-Obando, Eduardo (Frontiers in Public Health, 2023)
The increase in population aging establishes new risk scenarios in the face of the intensification of disasters due to climate change, however, previous experiences and collective memory would generate opportunities for older people to acquire adaptive and coping capacities in the face of these events. Objective: To analyze the theoretical-methodological characteristics presented by the studies carried out between the years 2012-2022 about the experience and collective memory of the elderly in the face of climate change. Method: A systematic literature review (SLR) was carried out following the guidelines of the PRISMA statement. The databases consulted were Web of Science, Scopus, EBSCO host and Redalyc, selecting 40 articles in Spanish, English and Portuguese. Results: The importance of experience and collective memory in the face of disasters as an adaptive factor in older people was identified. In addition, sharing experiences allows them to give new meaning to what happened, emphasizing confidence in their personal resources and self-management capacity, fostering perceived empowerment. Discussion: It is essential that in future studies the knowledge provided by the elderly can be privileged, recognizing the importance of their life histories, favoring the active role in their own development and well-being.